The Strategy of Typical Islamic Boarding Schools in Preparing Moderate and National-Minded Kyai-Ulama Cadres - Mar’atus Sholeha; Titiek Rohanah Hidayati; Khotibul Umam; Agus Supriadi (Institut Agama Islam An-Nawawi Purworejo, 2024)
This study aims to describe the concept of Moderate and National-minded Kyai-ulama, the Learning Process, and the strategies applied in preparing Cadres of Moderate and National-minded Kyai-ulama. This research was conducted in Ma'had Aly Nurul Qadim Paiton Probolinggo. The approach and type of research used are qualitative case studies. Data collection using interview, observation, and documentation methods. Data analysis using Miles and Huberman's theory. Researchers use triangulation techniques and sources to test the data's validity. The results of this study are: First, moderate and national-minded scholars, according to Ma'had Aly Nurul Qadim, are scholars who adhere to the concept of أدعوا الى سبيل ربك بالحكمة والموعظة الحسنة implications of the verse First, not too right and left, Second, not imposing, Third, Marrying culture with religion. Second, the Learning Process applied by Ma'had Aly Nurul Qadim Probolinggo in preparing Moderate and National-Minded Kyai-ulama Cadres is to practice a student-based learning process instead of lecturer-based. Third, there are five strategies for Ma'had Aly Nurul Qadim Probolinggo in preparing Moderate and National-Minded Kyai-ulama Cadres. First, boarding students. Second, apply the democratic system in the learning process. Third, encourage bahtsul masail activities. Fourth, hold a national seminar. Fifth, community service is based on local culture.